2003
DOI: 10.1128/aac.47.1.383-386.2003
|View full text |Cite
|
Sign up to set email alerts
|

gyrA Mutations in Ciprofloxacin-Resistant Bartonella bacilliformis Strains Obtained In Vitro

Abstract: We isolated and characterized mutants of Bartonella bacilliformis that are resistant to the fluoroquinolone antibiotic ciprofloxacin, which targets the A subunit of DNA gyrase. Mutants had single point mutations in the gyrA gene that changed either Asp-90 to Gly or Asp-95 to Asn and had 3-or 16-fold higher resistance, respectively, to ciprofloxacin than did wild-type B. bacilliformis. Asp-95 is homologous to Asp-87 of Escherichia coli GyrA and is a common residue mutated in fluoroquinolone-resistant strains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 23 publications
2
39
0
5
Order By: Relevance
“…However, its homologues, including Asp-90 in Bartonella bacilliformis and Asp-81 in Bacteroides fragilis, have been reported previously [23,24]. In our study, Asp was substituted with Asn at position 81 alone in strain SH64 with a moxifloxacin MIC of 32 mg/L.…”
Section: Discussionmentioning
confidence: 63%
“…However, its homologues, including Asp-90 in Bartonella bacilliformis and Asp-81 in Bacteroides fragilis, have been reported previously [23,24]. In our study, Asp was substituted with Asn at position 81 alone in strain SH64 with a moxifloxacin MIC of 32 mg/L.…”
Section: Discussionmentioning
confidence: 63%
“…and H75Y (L4 protein) [107] Azithromycin A2058G (16S rRNA) [112] Gentamicin A1408G ‡ (16S rRNA) [113] Pradofloxacin S83V (gyrA) [112] Enrofloxacin S83V (gyrA) [112] Ciprofloxacin S83A (gyrA) [102] Bartonella bacilliformis Erythromycin A2058G (23S rRNA) [109] Ciprofloxacin D87N, S83A (gyrA) [102,109,124] Rifampicin S531F (rpoB) [109] Bartonella quintana Erythromycin GRARHSSAR § (L4 protein) [110] Rifampicin S83A (gyrA) [126] Ciprofloxacin S531F (rpoB) [ Another recent study demonstrated that B. henselae isolates obtained from cats became resistant to pradofloxacin and enrofloxacin (both are fluoroquinolones that are mainly used in veterinary medicine) after different numbers of passages [112]. Compared with the parental B. henselae strains, the pradofloxacin-and enrofloxacin-resistant mutants had an amino acid change from serine to valine at position 83 (E. coli numbering) in gyrA [112].…”
Section: Bartonella Henselaementioning
confidence: 99%
“…Variations in the QRDR region were found in species with natural resistance to fluoroquinolones [119][120][121][122][123]. In 2003, Minnick et al isolated and characterized B. bacilliformis mutants that were resistant to ciprofloxacin [124]. In 2007, we obtained a ciprofloxacin-resistant strain of B. bacilliformis in vitro; the strain contained a transition from C to T at position 549 (E. coli numbering) of the gyrA gene, encoding the predicted amino acid change Asp 87→Asn in gyrA [109].…”
Section: In Vitro Antibiotic Resistancementioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t Moreover, in vitro-selected ciprofloxacin-resistant B. bacilliformis mutants that possess the amino acid changes D90G or D95N in GyrA have been reported [3].…”
Section: Page 2 Ofmentioning
confidence: 99%